2014
DOI: 10.1371/journal.pone.0094383
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine Secretion in Drosophila Salivary Glands: Subcellular Origin, Dynamics, and Identification of Secretory Proteins

Abstract: In contrast to the well defined mechanism of merocrine exocytosis, the mechanism of apocrine secretion, which was first described over 180 years ago, remains relatively uncharacterized. We identified apocrine secretory activity in the late prepupal salivary glands of Drosophila melanogaster just prior to the execution of programmed cell death (PCD). The excellent genetic tools available in Drosophila provide an opportunity to dissect for the first time the molecular and mechanistic aspects of this process. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 115 publications
6
50
0
1
Order By: Relevance
“…Farkas et al . () suggest that Drosophila salivary glands could be a useful model system to study apocrine secretion, especially for understanding the sorting of cellular components for secretion and retention within the cell. However, the eventual cell death of this epithelium after major apocrine secretory processes makes it substantively different from the lactating mammary cell, which must continue apocrine secretion for days, weeks or even months.…”
Section: Discussionmentioning
confidence: 99%
“…Farkas et al . () suggest that Drosophila salivary glands could be a useful model system to study apocrine secretion, especially for understanding the sorting of cellular components for secretion and retention within the cell. However, the eventual cell death of this epithelium after major apocrine secretory processes makes it substantively different from the lactating mammary cell, which must continue apocrine secretion for days, weeks or even months.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that at 1-6/7 h APF, the glands undergo intense vacuolation associated with complex endosomal trafficking, and then, at about 8-10 h APF, they display apocrine secretion (Farkaš et al, 2014(Farkaš et al, , 2015. In order to provide a physiological explanation for the relationship of these new cytological observations to the previously well-characterized chromosomal puffing patterns, we measured the respiratory metabolism of the Drosophila SG during the nonfeeding prepupal period.…”
Section: Introductionmentioning
confidence: 95%
“…During the next set of cytological stages characterized by neutralization and disappearance of the vacuoles, apocrine secretion and PCD ( Fig. 2; Farkaš et al, 2014Farkaš et al, , 2015, the regular metabolic decline, initiated already in the wandering larval stage and interrupted temporarily during pupariation, continues until the complete dissolution of the SG.…”
Section: Relationships Between Respiratory Metabolism and Cytologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we have described massive apocrine secretion in 8–10 h prepupal salivary glands of Drosophila (Farkaš et al . ). Here, we have used genetic tools and confocal microscopy to more precisely characterize the range of cellular processes that occur between 0 and 7/8 h of prepupal development.…”
Section: Introductionmentioning
confidence: 97%